Measuring Emission of Agricultural Greenhouse Gases and Developing Mitigation Options using Nuclear and Related Techniques Applications of Nuclear Techniques for GHGs - Zaman, Mohammad; Heng, Lee; Müller, Christoph (Springer Nature, 2021)
This open access book is an outcome of the collaboration between the Soil and Water Management & Crop Nutrition Section, Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture, Department of Nuclear Sciences and Applications, International Atomic Energy Agency (IAEA), Vienna, Austria, and the German Science Foundation research unit DASIM (Denitrification in Agricultural Soils: Integrated control and Modelling at various scales) and other institutes. It presents protocols, methodologies and standard operating procedures (SOPs) for measuring GHGs from different agroecosystems and animals using isotopic and related techniques that can also be used to validate climate-smart agricultural practices to mitigate GHGs. The material featured is useful for beginners in the field wanting an overview of the current methodologies, but also for experts who need hands-on descriptions of said methodologies. The book is written in form of a monograph and consists of eight chapters.